University students’ perspectives on integrating generative AI into English language learning - Yong-Jik Lee; Masashi Otani (Institute of Advanced Engineering and Science, 2026)
This study examines university students’ perspectives on integrating artificial intelligence (AI) into their English language learning, with a focus on cognitive and affective factors. Using a mixed method, the research collected quantitative data from surveys and qualitative insights from individual interviews with English language learners (ELLs). Survey results showed that ELLs recognized the technical capabilities of generative AI, particularly its extensive and dynamic database and practical translation functions. ChatGPT demonstrated clear benefits in terms of its emotional impact, including enhancing task efficiency and motivating learners. ELLs appreciated its ability to save time and foster engagement, but its influence on building confidence in language learning was less pronounced. In the cognitive domain, ELLs highlighted both opportunities and risks. While recognizing the potential for improved efficiency, concerns emerged about overreliance on generative AI, reduced independent thinking, and the possibility of facilitating academic dishonesty. Future research should focus on developing guidelines and best practices to maximize the benefits of generative AI tools while addressing their limitations.